The Emerging Importance of Liver Sinusoidal Endothelial Cells in Regulating Injury during Machine Perfusion of Deceased Liver Donors - Bhogal, Ricky H.; Mergental, Hynek; Mirza, Darius F.; Afford, Simon C. (Seminars in Liver Disease, 2018)
While majority of liver transplants worldwide continue to be performed using deceased donor organs, the demands for donor livers continues to exceed the current supply. In an attempt to maximize the number of potentially usable donor livers and expand the current donor pool, there is intense global research by various groups exploring the role of machine perfusion in the liver transplantation, particularly with respect to the machine perfusion of extended-criteria liver donors. In this review, the authors summarize the current field of machine perfusion strategies as applied to deceased donor liver transplantation and how therapeutic targeting of the liver sinusoidal endothelial cell may improve the quality of donor livers.
Keywords: liver transplantation; liver sinusoidal endothelial cells; machine perfusion; donor liver; ischemia-reperfusion injury